2008
DOI: 10.1093/nar/gkn616
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Xenopus DNA2 protein as a major nuclease for the 5'->3' strand-specific processing of DNA ends

Abstract: The first step of homology-dependent DNA double-strand break (DSB) repair is the 5′ strand-specific processing of DNA ends to generate 3′ single-strand tails. Despite extensive effort, the nuclease(s) that is directly responsible for the resection of 5′ strands in eukaryotic cells remains elusive. Using nucleoplasmic extracts (NPE) derived from the eggs of Xenopus laevis as the model system, we have found that DNA processing consists of at least two steps: an ATP-dependent unwinding of ends and an ATP-independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
73
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 38 publications
7
73
0
1
Order By: Relevance
“…In agreement with these findings, it has been observed that cells depleted of both BLM and EXO1 show a reduction in the formation of RPA foci in response to DSBs and are defective in DSB repair by HR (16,19). However, studies using Xenopus egg extracts and purified proteins have shown that Dna2 mediates DNA end resection together with WRN rather than BLM (21)(22)(23). This discrepancy prompted us to investigate the role of WRN in DNA end resection in human cells.…”
mentioning
confidence: 69%
“…In agreement with these findings, it has been observed that cells depleted of both BLM and EXO1 show a reduction in the formation of RPA foci in response to DSBs and are defective in DSB repair by HR (16,19). However, studies using Xenopus egg extracts and purified proteins have shown that Dna2 mediates DNA end resection together with WRN rather than BLM (21)(22)(23). This discrepancy prompted us to investigate the role of WRN in DNA end resection in human cells.…”
mentioning
confidence: 69%
“…However, in contrast to FEN1, Dna2 is an essential gene in yeast, suggesting that other proteins, including FEN1, cannot compensate for its loss in DNA replication or that it possesses functions beyond its role in Okazaki fragment processing. In agreement with this, genetic and biochemical studies have implicated Dna2 in DNA double-strand break (DSB) repair, telomere regulation, and mitochondrial function (8,10,15,26,38,44,45).Analysis of Dna2 in yeast revealed that it undergoes dynamic cell cycle localization. Dna2 localizes to telomeres during G 1 , relocalizes throughout the genome in S phase, and moves back to the telomere during late S/G 2 , where it participates in telomere replication and telomerase-dependent telomere elongation (10).…”
mentioning
confidence: 71%
“…These phenotypes may be explained by recent work demonstrating that Dna2 plays an important role in 5Ј-end resection following DSBs. Indeed, upon induction of DSBs and initiation of 5Ј-end resection by the Mre11-Rad50-Xrs2 complex, Dna2 and Sgs1 cooperate to further degrade the 5Ј end, creating long 3Ј strands essential for homologous recombination (26,45). Finally, while dna2⌬ mutations are lethal in budding yeast, the dna2⌬ pif1-m2 (nuclear PIF1) double mutations rescue dna2⌬ lethality but produce a petite phenotype, suggesting that Dna2 is also involved in mtDNA maintenance (8).…”
mentioning
confidence: 99%
“…Helicase activities of Xenopus laevis and human Dna2 were considered to be either non-existent or extremely weak (22,35). The robust nuclease activity of Dna2 tends to obscure detection of its unwinding property.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the helicase activity of yeast Dna2 is dispensable under certain growth conditions, its endonuclease activity is essential. How-ever, growth defects in the helicase mutants demonstrate that the helicase is important for Dna2 physiological function in vivo (17 The endonuclease activity of Dna2 has been shown to play a role in Okazaki maturation (20), telomere maintenance (21), double strand break repair (22)(23)(24)(25), long patch base excision repair (26), and aging (27). However, with the exception of showing unwinding of G4 quartets by Dna2 helicase (28) and showing that mutation of the helicase relatively few studies have been focused on understanding its roles.…”
mentioning
confidence: 99%